Pemikiran Al-Qardhawi Tentang Metode Memahami Hadis dengan Membedakan Antara Sarana yang Berubah dan Tujuan yang Tetap dalam Hadis - Atabik, Ahmad (RIWAYAH, 2015)
This article describes the thinking of al-Qaradhawi on methods to understand the hadith to distinguish between means and goals remain unchanged in the hadith. This article begins the biography setting of al-Qaradhawi. Al-Qaradhawi has the full name of Abdullah Yusuf al-Qaradhawi. Saft} Tura>b is the birthplace of al-Qaradhawi, a small village which is one of the beautiful villages of Egypt contained in Gharbiyah province, its capital is Tanta. The work of al-Qaradhawi’s “Kaifa Nata’a> mal ma’a al-Sunnah al-Nabawiyya” is a magnum opus in the study of hadith. In this work, al-Qaradhawi sparked about the various methods and principles to understand the traditions of the Prophet with a proper understanding. Hadith as an interpretation of the Qur’an in the practice or application of Islamic teachings in a factual and ideal, has a way of a comprehensive, balanced and facilitating (taisi>r). In the end, this article specifically describes methods of al-Qaradhawi, and their application in examples of hadith of the Prophet. The purpose of writing this article is to understand the tradition, should be able to distinguish between means and goals or objectives. Most errors are usually considered. That is what should be the purpose of our guidance is not a means, which can be changed at any time.